Nest of serpents - Jobling, Curtis (Jobling, Curtis. Wereworld, 2015)
War continues to ravage the kingdom of Lyssia. Drew, the rightful heir to the Werelord throne, is battling the Ratlord and the Crowlords. When the evil Wereserpent unexpectedly returns, Drew and his allies now face three powerful opponents. But suddenly Drew's friend Hector embraces the powers of the dark magistry and turns into the most dangerous enemy of all.